Fire occurrence and the current state of palaeofire reconstructions based on sedimentary charcoal from natural archives in Poland - Bonk, Alicja (Bulletin of Geography. Physical Geography Series, 2019)
Due to rising temperatures worldwide many areas are threatened with increasing numbers of fire occurrence. Poland is among these areas and is projected to experience over the next century an increase in both heat stress and wildfire activity with the potential to turn its fire-resistant forests into fire-prone forests. This paper aims to provide an introduction to the conditions favourable to fire occurrence in Poland, summarising the research on sedimentary charcoal analysis and reviewing fire reconstructions based on natural archives from Poland. Here, natural wildfires occurred at the beginning of the Holocene but, due to changes in climate (wetter summers) and vegetation after 6550 bc, the main trigger of fire occurrence became human activity, mainly as a result of forest clearance for agrarian purposes. However, there is evidence that prolonged droughts also triggered wildfires. Over recent decades, according to existing data, arson (44.85%) and negligence (34.43%) have been the most common causes of fire occurrence in Poland.